1992
DOI: 10.1152/jappl.1992.72.3.858
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous and exogenous catalase in reoxygenation lung injury

Abstract: Reexpansion pulmonary edema parallels reperfusion (reoxygenation) injuries in other organs in that hypoxic and hypoperfused lung tissue develops increased vascular permeability and neutrophil infiltration after reexpansion. This study investigated endogenous lung catalase activity and H2O2 production during hypoxia (produced by lung collapse) and after reoxygenation (resulting from reexpansion), in addition to assessing the effects of exogenous catalase infusion on the development of unilateral pulmonary edema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 0 publications
0
23
0
1
Order By: Relevance
“…Only Cremer et al (12) found a limitation of pulmonary reperfusion injury by giving the oxygen free radical scavengers in combination of catalase and superoxide dismutase during perfusion and continuously during the first 20 min in a canine model of heterotopic heart-lung transplantation. The main inability of exogenous catalase administration to provide beneficial physiological effects lies in the specific effects of endogenous lung catalase activity (25). Catalase is localized in the intracellular compartment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only Cremer et al (12) found a limitation of pulmonary reperfusion injury by giving the oxygen free radical scavengers in combination of catalase and superoxide dismutase during perfusion and continuously during the first 20 min in a canine model of heterotopic heart-lung transplantation. The main inability of exogenous catalase administration to provide beneficial physiological effects lies in the specific effects of endogenous lung catalase activity (25). Catalase is localized in the intracellular compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts to limit I/R injury have been employed, e.g., elimination of neutrophil granulocytes (an important source of ROS generation) and/or maximization of antioxidative capacity under supply of antioxidative enzymes, vitamins, and others (23,24,46). The results, however, have been inconsistent (12,25,26,47). This might be because of insufficient uptake into the endothelial cells (10,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only Cremer et al demonstrated a diminished pulmonary reperfusion injury in a canine model of heterotopic heart-lung transplantation by using a combination of catalase and superoxide dismutase administered during flush-perfusion and the first 20 min of reperfusion [19]. The main inability of exogenous catalase administration to provide beneficial physiologic effects lies in the specific physical location of endogenous lung catalase activity [21]. Catalase is localised to the intracellular compartment and Muzykantov et al have shown that biotinylated catalase has a poor uptake into the intracellular compartment of the pulmonary endothelium [22].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with that idea, it is known that the interaction between adherent neutrophils and endothelial cells regulates lung permeability in RPE (10) and that reactive oxygen species (ROS) produced by neutrophils increase pulmonary endothelial permeability. On the other hand, using an animal RPE model Jackson et al (14) found that exogenous catalase does not prevent RPE, which eliminates extracellular hydrogen peroxide as an important contributor, but they did detect endogenous lung catalase activity and hydrogen peroxide release. This supports the idea that endogenous production of ROS is a key contributor to RPE.…”
mentioning
confidence: 95%